Renaissance of project marketing: Avenues for the utilisation of digital tools - Sebastian Toukola; Matias Ståhle; Tommi Mahlamäki (Project Leadership and Society, 2023)
Project marketing differs from other business-to-business (B2B) marketing processes due to its uniqueness and complexity of offers, which in turn makes the management of project marketing challenging. Although the use of digital tools has received increased attention in research on other forms of B2B marketing, few previous studies have concentrated on the project marketing view. To fill this gap, we conducted a two-phase qualitative study considering explicit digital tools for the project supplier's marketing process. Based on the results of this study, we identify a list of 117 digital tools that can be used in project marketing, which we divide into 11 categories. As our main contribution, we offer insights into suitable tools that suppliers can use in each step of the project marketing process. This study contributes novel knowledge about digital project marketing by offering an understanding of digital tools and their use in the project marketing process.